Pengaruh Pendapatan Premi dan Hasil Investasi Dana Terhadap Cadangan Dana Tabarru - Ilik Bunadi; Ragil Dzikri Noor Alam (Cakrawala Repositori IMWI, 2019)
This research aimed to figured out the effect of premium income and investment return toward tabarru fund reserves. The data collection method used in this study was documentation by getting the data of financial statement published by the company. The population used in this study was sharia insurance company which listing Assosiations Sharia Insurance Indonesia(AASI) along period of 2012 – 2016. The sample was taken using simple random sampling method which generated 61 samples of year 2012 – 2016. Moreover, the data analysis technique used was descriptive statistics. Also, this study used clasical assumption test : normality test, multikolinearity test, autokorelation test, and heteroskedastisitas test. Hypothesis testing using multiple liniear regression analysis. The result of this study showed that the one independent variable which consisted of premium income signifcanly affect the tabarru fund reserves. Meanwhile, the other one variable (investment return)had no significan affect towards the tabarru fund reserves. This study was conducted only in one sharia insurance company.